Comparison of surgical castration at birth versus immunocastration on behavioural response and blood parameters (testosterone and cortisol) in Holstein fattening bulls - Pérez Linares, Cristina (2020)
The behavioural response and blood parameters were compared in immunocastrated and surgically castrated bovine males. In total, 720 Holstein males, 7-8 months old and approximately 240 kg body weight were used. One group was immunocastrated by vaccination with Bopriva (commercial anti-GnRH vaccine) on days 1, 21, 101 and 181 days of the fattening and the other group was surgically castrated at birth. Blood samples were taken on vaccination days for testosterone determination and on days 181 and during slaughtering to analyse blood cortisol. Sexual behaviour (mounts and flehmen signs) and aggressive (threats and head butting) and social behaviour (sniffing, grooming, lowered head, and vocalization) were evaluated, finding no significant differences between treatments. Testosterone concentration in both treatments was below 1 ng/ml in all samples. Cortisol levels on day 181 of fattening were lower (p<0.05) with respect to the day of slaughtering in both treatments. Slaughter weight (242 days fattening) was 595.0 kg in immunocastrated males and 620.74 kg in surgically castrated males.